PENGARUH SENAM JANTUNG SEHAT TERHADAP NILAI TEKANAN DARAH PADA LANSIA PENDERITA HIPERTENSI: THE EFFECT OF HEALTHY HEART EXERCISE ON BLOOD PRESSURE VALUES IN ELDERLY HYPERTENSION PATIENTS - Antri Ariani; Meliana Fuji Lestari; Andria Pragholapati (Akademi Keperawatan Yarsi Samarinda, 2020)
The disease is often experienced by the elderly in Indonesian according to Department of Health Houshold Survey on Health is hypertension with the incidence by 15,7%. Based on data from Department Health Office in Sumedang district, The highest cases of non-communicable diseases is hypertension by 29,6%. This reseach as a purpose determine the effect of a healthy heart gymnastics on the value of blood pressure in elderly hypertensive patients in Community Health Center DTP Jatinangor 2015. This type of research that is quasi experiment with an approach one group pre and postest design. The reseach population by 24 respondents specified by purposive sampling techniques. The reseach results revealed an average value of systolic blood pressure for 3 weeks before a healthy heart gymnastics is 142,8 mmHg and diastolic 94,2 mmHg, while after being given for 3 weeks healthy heart gymnastics the average value of systolic blood pressure was 129.6 mmHg and 86.3 mmHg diastolic. Test results paired T-Test obtainable ρ value 0.000 less than 0.05 for systolic and diastolic blood pressure, means there is healthy heart gymnastics influence on the value of blood pressure in elderly hypertensive patients in Community Health Center DTP Jatinangor